A review of the anthropometric characteristics, grading and dispensation of junior and youth Rugby Union players in Australia - Patton, D. A.; McIntosh, A. S.; Denny, G. (Sports Medicine, 2016)
The grading of Australian junior and youth rugby union players has received substantial media attention in recent years. Media reports have focussed on size mismatches observed between players, especially players with Polynesian heritage, and the concerned parents who fear for the safety of their child owing to perceived mismatches. Although such concerns are well meaning, few media reports recognise the need for substantial evidence to determine the best grading system for junior and youth rugby union players. The current study reviewed relevant literature pertinent to the grading and dispensation of junior and youth rugby union players. Using primary and secondary search strategies, a total of 33 articles reporting the anthropometric characteristics of junior and youth rugby players were identified. Anthropometric data from the literature were compared with normative population data and currently used dispensation criteria. Junior and youth rugby players were found to be taller and heavier than normative population data. Current dispensation criteria, in terms of body mass, were found to vary and it is suggested that criteria be revised and standardised across rugby unions throughout Australia. Although it is acknowledged that other factors are important for grading players, anthropometric characteristics should be considered as potential dispensation criteria to supplement current age-based grading for junior and youth rugby union players. Measuring the body mass and stature of each junior player upon pre-season registration is suggested, which would provide data to establish valid dispensation criteria for the following season.